Rapamycin-Loaded mPEG-PLGA Nanoparticles Ameliorate Hepatic Steatosis and Liver Injury in Non-alcoholic Fatty Liver Disease - Zhao, Ruifang; Zhu, Meilin; Zhou, Shuang; Feng, Weiyue; Chen, Hanqing (Frontiers in Chemistry, 2020)
Nonalcoholic fatty liver disease (NAFLD) is characterized by excessive lipid accumulation and liver injury, and is the leading causes of chronic liver disease worldwide. There is an urgent need to develop novel pathophysiology-oriented therapy in human. Rapamycin (RAPA) has been recognized as a promising drug for alleviating hepatic steatosis on NAFLD, but the poorly water-soluble properties and side effects of RAPA limit their clinical use. In this study, we aimed to investigate the in vitro and in vivo therapeutic efficacy of biodegradable mPEG-PLGA polymers loaded with RAPA (NP-RAPA) on NAFLD. NP-RAPA were prepared by a green process using an emulsion/solvent evaporation method, the therapeutic efficacy on NAFLD were investigated on HepG2 cells incubated with oleic acid (OA) and in the livers of mice with NAFLD induced by high-fat diet (HFD). Compared with free RAPA, NP-RAPA significantly reduced lipid accumulation in HepG2 cells, and obviously ameliorated hepatic steatosis and liver injury in mice though enhancing the therapeutic efficacy of RAPA through reducing SREBP-1c-dependent de novo lipogenesis (DNL) and promoting PPARa-mediated fatty acid oxidation. This study suggests that mPEG-PLGA can be used as the potential therapeutic strategy and novel drug delivery for improving the efficacy of rapamycin for treatment of NAFLD.